(3ZGjI GdHjGf fGOQI GdReGf aj BNQ GdChGfs - (3CejQ cGJH Hf CejQ YeQ Hf CejQ ZGRj GdaGQGHqj GdEJbGfj GdYejOj GdMfaj, CHh MfajI, bhGe GdOjf, J (B758 (3g`s; (3Ydj Hf CHj HcQ Hf YHO GdLdjd GdaQZGfj GdeQZjfGfj, CHh GdMSf HQgGf GdOjf,J (B593 (3g` s
(3ChdgG (B:s
(3HGH ai GdJhcjd s
(3BNQgG (B:s
(3HGH OYhi GdfSH s
(3GdfSNI HgG MhGTs
(3ef GdfSNI faSgGs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3Gdabg GdMfajs